2001
DOI: 10.1021/ma0101714
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism of Poly(di-n-hexylsilane) in Solution Revisited

Abstract: Solutions of poly(di-n-hexylsilane) in hexane, after aging for 5 days, exhibit on cooling two long-wavelength absorption bands at 357 and 368 nm, in addition to the normal high-temperature band at 320 nm. These UV absorptions probably represent different conformations of the polymer chain and so provide evidence for the simultaneous presence in solution of three different conformational forms. This is the first time such an observation has been made for a polysilanes and perhaps for any polymer.The UV thermoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 13 publications
1
30
0
3
Order By: Relevance
“…[1][2][3][4] They are sensitive to the backbone conformation and as ar esult lead to phenomena such as thermochromism, [5][6][7][8][9] piezochromism, [10,11] electrochromism, [12] ionochromism, [13,14] and solvatochromism. [15] Also their single-molecule electrical conductivity appearst od epend on conformation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] They are sensitive to the backbone conformation and as ar esult lead to phenomena such as thermochromism, [5][6][7][8][9] piezochromism, [10,11] electrochromism, [12] ionochromism, [13,14] and solvatochromism. [15] Also their single-molecule electrical conductivity appearst od epend on conformation.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Their intense electronic absorption in the near UV was found to be sensitive to the electronic nature of the substituents and the conformation of the silicon backbone, as reflected in the thermochromism, [2] solvatochromism, [3] and ionochromism [4] of some oligosilanes. Recent studies on linear derivatives with discrete conformations have shown that sconjugation is more effective in an anti-conformation (Si-SiSi-Si dihedral angle w = 1808) than in conformations with small dihedral angles, such as syn, cisoid, or even gauche (w = 0-608).…”
mentioning
confidence: 99%
“…MeSi(SiMeCl 2 ) 3 (1) was treated with 3 equivalents of KSi(SiMe 3 ) 2 Me at À78 8C. The reaction proceeds regio-and diastereoselectively yielding the l,l-form of 2 as the main product.…”
mentioning
confidence: 99%
“…MeSi(SiMeCl 2 ) 3 (1) wurde zunächst mit 3 ¾quivalenten KSi(SiMe 3 ) 2 Me bei À78 8C in einer regiound diastereoselektiven Reaktion zu l,l-2 umgesetzt. [7] Die anschließende Hydrolyse in Gegenwart von NH 4 (NH 2 COO) liefert racemische Mischungen der beiden möglichen Diastereomere l,u-3 und l,l-3 (siehe die Hintergrundinformationen).…”
unclassified
“…[10] Ungewöhnlich ist das unterschiedliche UV-spektroskopische Verhalten beider Diastereomere. Die Absorptionskurven von l,u-3, l,l-3 und dem Strukturanalogon MeSi[SiMe 2 Si-(SiMe 3 ) 2 Me] 3 (4) sind in Abbildung 3 gezeigt. Das Absorptionsmaximum von l,u-3 bei 282 nm (e = 3.7 10 4 ) mit einer Schulter bei ca.…”
unclassified